STRATEGI CUSTOMER RELATIONSHIP MANAGEMENT DALAM MENINGKATKAN LOYALITAS PELANGGAN DI ERA DIGITAL: SEBUAH KAJIAN PUSTAKA - Alexander Langgeng, Vincent; Setiawan, Alexander (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The study employs systematic literature review methodology combined with bibliometric analysis, examining peer-reviewed publications from Scopus and Web of Science databases published between January 2021 and January 2026, following PRISMA 2020 guidelines. Data extraction utilized structured forms capturing study characteristics, research methodology, substantive focus, and key findings, while quality appraisal employed JBI Critical Appraisal Checklist and CASP Checklists. Thematic synthesis using Braun and Clarke's six-step framework combined with bibliometric analysis using CiteSpace and VOSviewer software identified major themes and research trends. Results reveal that trust emerges as the dominant mediation mechanism with indirect effect coefficient of 0.34 compared to satisfaction at 0.14, indicating that building trust-based relationships is strategically more important than short-term satisfaction optimization. AI-driven personalization demonstrates 25 percent customer retention improvement, while effective omnichannel integration significantly enhances loyalty through dual mediation pathways. Findings highlight that successful CRM implementation in emerging markets requires mobile-first, cloud-based solutions with simultaneous emphasis on trust-building through data transparency. Future research should explore how cultural preferences and demographic characteristics in emerging markets interact with CRM strategies to generate heterogeneous loyalty outcomes and investigate long-term sustainability of AI-driven personalization relative to ethical concerns and privacy protection.